Automation of check-in procedures in the tourism industry - Marques, João Martinho (2019)
This report takes advantage of Web and IoT technology to remove the necessity of 3th people into the check-in procedures. The innovation has the objective to improve the accommodation sector in Tourism and Travel activities. For choosing of the most suitable technology, a careful analysis was performed about the target audience and the possible technologies. Then, a business plan was developed to explain how the product can be profitable, generate value to society and present itself as an innovation. Only after that, MVP was developed to test the viability of this business model. The MVP consisted on platform and locker that allow the user to manage and use their desired accesses to the mechanical engineering laboratories in university of Aveiro.